1989
DOI: 10.1126/science.2658056
|View full text |Cite
|
Sign up to set email alerts
|

Delay of Gratification in Children

Abstract: To function effectively, individuals must voluntarily postpone immediate gratification and persist in goal-directed behavior for the sake of later outcomes. The present research program analyzed the nature of this type of future-oriented self-control and the psychological processes that underlie it. Enduring individual differences in self-control were found as early as the preschool years. Those 4-year-old children who delayed gratification longer in certain laboratory situations developed into more cognitivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

58
2,106
7
82

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,856 publications
(2,253 citation statements)
references
References 35 publications
58
2,106
7
82
Order By: Relevance
“…The DGT was administered during the 54-month laboratory visit and was modeled on Mischel's self-imposed waiting task (Mischel, Shoda, & Rodriguez, 1989).…”
Section: Delay Of Gratification Taskmentioning
confidence: 99%
“…The DGT was administered during the 54-month laboratory visit and was modeled on Mischel's self-imposed waiting task (Mischel, Shoda, & Rodriguez, 1989).…”
Section: Delay Of Gratification Taskmentioning
confidence: 99%
“…Does the reverse reward task test for "self control"? Initially, studies on impulse control were mainly performed with humans (Mischel et al 1989;Russell et al 1991) and primates (Boysen and Berntson 1995;Boysen et al 1996;Silberberg and Fujita 1996;Kralik et al 2002;Genty et al 2004). Some authors have suggested that success in the reverse reward task may be interpreted as a form of "self control" thereby implying that in order to solve the task, some "awareness of self" needs to be involved (e.g.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The ability to control impulsive behaviour in order to acquire an overall long term beneWt has received a large amount of interest in studies on human and non-human animal behaviour (Mischel et al 1989;Genty et al 2004;Abeyesinghe et al 2005;Murray et al 2005;Genty and Roeder 2006;Wittmann and Paulus 2008). Impulse control may be advantageous in order to withhold an action that would have deleterious consequences in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In the classic 158 marshmallow test by Mischel et al (1989), pre-school children were encouraged to resist the 159 temptation of eating a single piece of their favourite confectionary while the experimenter was 160 absent from the room up to 15 minutes. In exchange, children who could successfully delay the 161 gratification would be offered two pieces of their preferred confectionary.…”
mentioning
confidence: 99%
“…The observation of 162 childrens' behavior revealed different cognitive strategies -by focusing on the 'hot' properties such 163 as the taste of the confectionary led the child to be more impulsive, while focusing on the 'cool' 164 properties such as the shape of the object or other types of distractions, children were able to wait 165 for longer. A remarkable finding is that the delay gratification measures of these pre-schoolers 166 could successfully predict their scholastic achievements as adolescents (Mischel et al, 1989). A 167 recent brain imaging study examined cognitive control strategies on a subset of the original study's 168 participants using a go/no-go paradigm (Casey et al, 2011).…”
mentioning
confidence: 99%